Open a world of possible real stories about the joy and power of reading - Robinson, Richard; Bridges, Lois
"188 distinct voices from every region of the country, including Alaska and Hawaii ... all celebrate reading for enriching their lives ..., and share a fervent wish that children around the world enjoy abundant access to books so that they too may 'live many parallel lives' and dream what may be possible for their own."